Literasi Hukum Anti-Bullying Berbasis KUHP Baru bagi Siswa di Negeri Ihamahu - A Rutman; A Tongkala; J Matakena; J Linansera; S Ferneyanan; S Batlayery; F Tutkey; F Souhoka (MAN 4 Kota Pekanbaru, 2026)
Bullying in school environments has become an increasingly serious issue among adolescents, with significant impacts on students’ psychological, social, and academic well-being. This study aims to strengthen students’ legal awareness of bullying through the socialization of the Indonesian Criminal Code (Law No. 1 of 2023) at SMP Negeri 43 Maluku Tengah, Negeri Ihamahu. The research employed a descriptive qualitative approach using participatory observation, involving 211 students across grades 1 to 3. The activity was conducted in four stages: preparation, implementation of socialization, discussion and interaction, and evaluation. The results indicate that prior to the activity, many students perceived bullying as a normal social interaction. However, after the socialization, students demonstrated improved understanding that bullying—whether physical, verbal, social, or cyber—can have serious consequences and may constitute a criminal act under the new Criminal Code. The study also highlights the effectiveness of a restorative justice approach in fostering empathy, responsibility, and behavioral change among students. This research contributes by integrating anti-bullying education with legal literacy, providing a more comprehensive preventive strategy to create a safe and supportive school environment.